Modeling information pathway of motor control using coherence analysis - Mat Safri, Norlaili (Institute of Electrical and Electronics Engineers, 2008)
Motor behavior can be guided by visual information. For example, hand actions were modified by visual cues that provided initial weight and size estimates of objects. Vision provides important inputs to the representational system which are linked not directly to motor outputs but are linked to cognitive systems. The visual and voluntary motor tasks are controlled by the brain signals which drive the cortical activity and perception. But the cortical activity are not driven by these external stimulus alone, relatively sensory information need to be integrated with various internal constraints such as planned actions, expectations, recent memories, etc. This paper presents C 3-EEG coherence analysis during two different visual tasks concurrent with isometric contraction of the first dorsal interosseous (FDI) muscle. The functional connection between different brain regions was investigated to model information pathway of motor control in humans.